(untitled) (Research, Society and Development, 2025)
Myofascial mobilization has been widely used in sports physical therapy due to its contribution to improving mobility and muscle function, both essential components of performance in amateur soccer, a modality characterized by a high prevalence of musculoskeletal injuries. This study aimed to evaluate the effectiveness of myofascial mobilization on flexibility and physical performance in amateur soccer athletes. An integrative literature review was conducted, including searches in scientific databases, following predefined inclusion and exclusion criteria and qualitative analysis of the eligible studies. The selected articles predominantly involved young athletes, mostly male, and linked to university or school teams. Most interventions consisted of self-myofascial mobilization techniques using foam rollers applied to major lower-limb muscle groups, assessed through tests such as sit-and-reach, vertical jump, and range-of-motion measurements. The synthesis of findings showed significant improvement in flexibility and, in some cases, in physical performance following the intervention. However, considerable heterogeneity in the applied protocols and a limited number of Brazilian studies specifically addressing the amateur population were observed. It is concluded that myofascial mobilization represents a potentially effective and accessible tool to optimize physical performance and prevent musculoskeletal dysfunctions in amateur athletes. Nevertheless, the lack of methodological standardization and limited representativeness of diverse athlete profiles underscore the need for broader and more well-designed future research.